A History of Accident and Emergency Medicine, 1948-2004 - Guly, H. author. aut Link
XVIII, 183 p.
Keywords: Accident and emergency departments are the doorway to the hospital for acutely ill and injured patients. Whereas casualty departments have existed for over 150 years, they were often poorly staffed and managed. This book describes the fight to create a new medical specialty of accident and emergency medicine against much opposition from established specialties. The specialty was first recognised in 1972. The book also charts the major developments that occurred in the first 30 years of the specialty.